PENERAPAN AKUNTANSI MANAJERIAL DALAM PENGAMBILAN KEPUTUSAN BISNIS UMKM PASCA INSENTIF PAJAK PANDEMI: STUDI DI SEKTOR KULINER - Rachmawati, Rahayu Nugraheni; Zahra Dinul Khaq (LPPM Universitas Sains Dan Teknologi Komputer, 2025)
The COVID-19 pandemic disrupted the operations and financial sustainability of Indonesia's culinary MSMEs, prompting the government to offer tax incentives as support. With the end of these incentives, businesses were pushed to adopt data-driven decision-making, despite only 18% of MSMEs having adequate financial record-keeping systems. Key challenges in post-pandemic adaptation include low accounting literacy, limited human resources, and complex regulations. This study examines the practices, barriers, and effectiveness of managerial accounting among 120 culinary MSMEs in Jakarta, Bandung, and Surabaya through a mixed-methods approach combining case studies, surveys, and in-depth interviews. Findings indicate that business decisions remain largely intuition-based, with accounting limited to basic cash flow recording. Major barriers involve lack of expertise, limited access to technology, and difficulties adjusting to regulations. However, some medium-scale MSMEs have started applying cost analysis and budget planning. This study contributes to the limited literature on post-incentive managerial accounting in the culinary sector and highlights the urgency for context-based training, simplified fiscal policy processes, and adoption of user-friendly accounting technologies. Practical recommendations include collaborative training programs, mentoring, and technical assistance to improve MSMEs’ financial capacity and decision-making through better financial management practices